2022
DOI: 10.1002/adma.202208782
|View full text |Cite
|
Sign up to set email alerts
|

Dual Immunostimulatory Pathway Agonism through a Synthetic Nanocarrier Triggers Robust Anti‐Tumor Immunity in Murine Glioblastoma

Abstract: with chemoradiation, Food and Drug Administration (FDA)-approved treatments such as intracavitary chemotherapy wafers, bevacizumab, and alternating electrical fields [1] with median survival times of approximately 15 months from diagnosis. [2] Numerous promising therapeutic modalities (targeted kinase inhibitors, anti-angiogenic treatments, immunotherapies) have been tested in advanced clinical trials without lasting success.There has been a resurgence of interest in therapeutic modalities that stimulate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…CANDI is a biocompatible succinyl‐cyclodextrin polymeric drug carrier with affinity for tumor‐associated macrophages. [ 38,40 ] It contains small molecule drugs such as TLR7/8 agonist (R848), cIAP inhibitor (Lcl‐161), and a JAK1 inhibitor (ruxolitinib). In vitro, the drug induces IL‐12 via the canonical and noncanonical NFkB pathways and by inhibiting IL4 signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CANDI is a biocompatible succinyl‐cyclodextrin polymeric drug carrier with affinity for tumor‐associated macrophages. [ 38,40 ] It contains small molecule drugs such as TLR7/8 agonist (R848), cIAP inhibitor (Lcl‐161), and a JAK1 inhibitor (ruxolitinib). In vitro, the drug induces IL‐12 via the canonical and noncanonical NFkB pathways and by inhibiting IL4 signaling.…”
Section: Resultsmentioning
confidence: 99%
“…CANDI Experiments: The synthesis of cyclodextrin nanoparticles (CANDI) was further developed from a previously reported method. [38,40] Fluorescent CANDI was prepared by attaching AF647 succinimidyl ester (ThermoFisher, 2 mg mL −1 in DMSO). The labeled nanoparticle was purified by buffer exchange into water against 10 kDa MWCO centrifugal filters (Amicon; 10 000 rcf for 5 min; 300 μL water per wash, 3-4×).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PFI group with the highest risk score was shown to have substantial connections with genes related to the immune response, regulation of in ammatory response, collagen-containing extracellular matrix, and signaling pathways regulating pluripotency of stem cells. All of these factors have a strong relationship with the antitumor response, the spread of tumor metastases, the development of drug resistance, and the progression of tumors [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in tumor‐associated myeloid cells has shown that dual NFkB pathway manipulation is effective and improves tumor control. [ 8 ] This prior work used a 37 nm carbohydrate platform (CANDI) to deliver multiple small molecule immune modulators to tumor‐associated macrophages and a lesser degree to DCs. Here we reasoned that an analogous strategy could be developed for dendritic cell‐targeted vaccines but would have to be based on lipid nanoparticles (LNP) to improve dsRNA delivery.…”
Section: Introductionmentioning
confidence: 99%